Impact of Volcanic Aerosols on the Hydrology of the Asian Monsoon and Westerlies‐Dominated Subregions: Comparison of Proxy and Multimodel Ensemble Means. Issue 18 (11th September 2020) - Zhuo, Z.; Gao, C.; Kirchner, I.; Cubasch, U.
Abstract: Proxy‐model comparisons show large discrepancies in the impact of volcanic aerosols on the hydrology of the Asian monsoon region (AMR). This was mostly imputed to uncertainties arising from the use of a single model in previous studies. Here we compare two groups of CMIP5 multimodel ensemble mean (MMEM) with the tree‐ring‐based reconstruction Monsoon Asia Drought Atlas (MADA PDSI), to examine their reliability in reproducing the hydrological effects of the volcanic eruptions in 1300–1850 CE. Time series plots indicate that the MADA PDSI and the MMEMs agree on the significant drying effect of volcanic perturbation over the monsoon‐dominated subregion, while disparities exist over the westerlies‐dominated subregion. Comparisons of the spatial patterns suggest that the MADA PDSI and the MMEMs show better agreement 1 year after the volcanic eruption than in the eruption year and in subregions where more tree‐ring chronologies are available. The MADA PDSI and the CMIP5 MMEMs agree on the drying effect of volcanic eruptions in western‐East Asia, South Asian summer monsoon, and northern East Asian summer monsoon (EASM) regions. Model results suggest significant wetting effect in southern EASM and western‐South Asia, which agrees with the observed hydrological response to the 1991 Mount Pinatubo eruption. Analysis on model output from the Last Millennium Ensemble project shows similar hydrological responses. These results suggest that the CMIP5 MMEM is able to reproduce the impact of volcanic eruptions on the hydrology of the southern AMR. Key Points: Proxy and multimodel ensemble means agree (disagree) on post volcanic hydro‐responses over the Asian monsoon (westerlies)‐dominated subregion Better agreement of spatial hydrological patterns is suggested 1 year after the eruption and in subregions with more tree‐ring data Multimodel ensemble means can reproduce the hydrological response to volcanic perturbations in the southern Asian monsoon region